Effect of H2S on endothelial barrier function impairment in anorectal vascular plexus caused by deoxycholic acid - Yan, Han; Li, Ya-Lun; Pan, Shao-Rong; Ma, Yuan-Yuan; Zhu, Jing; Wang, Peng-Yuan; Chen, Ze-Yang (Frontiers in Medicine, 2025)
IntroductionAs a vascular-related disease, hemorrhoids cause pathological changes, such as abnormal dilation in the anorectal vascular plexus (AVP), which may be closely related to injury to vascular endothelial barrier function (VEBF). Elevated deoxycholic acid caused by a high-fat diet can impair intestinal barrier function. However, the effect of VEBF impairment in AVP caused by DCA is unclear. The aim of our study was to investigate the effects of DCA and GYY4137 on the VEBF in AVP and to explore the pathogenesis of hemorrhoids and new treatment ideas.MethodsA HUVECs monolayer model and mouse model were generated with a high DCA concentration and used to investigate the effect of GYY4137 on SDC-induced VEBF disruption in AVP and the underlying mechanism.ResultsIn the HUVECs monolayer model, DCA significantly increased the permeability of the monolayer and altered the distribution of tight junction proteins (TJPs) by increasing the levels of myosin light chain kinase and myosin light chain phosphorylation. GYY4137 pretreatment significantly improved DCA-induced VEBF dysfunction. GYY4137 can also increase resistance to SDC-induced VEBF injury and improve the distribution of TJPs in the AVP in mouse model.ConclusionGYY4137 can improve the distribution of TJPs by inhibiting the activation of the MLCK-P-MLC2 signaling pathway induced by DCA, thereby protecting the VEBF in AVP, which may be applied to hemorrhoids therapy in the future.